Subdiagrams of Bratteli Diagrams Supporting Finite Invariant Measures - Bezuglyi, S.; Karpel, O.; Kwiatkowski, J. (Журнал математической физики, анализа, геометрии, 2015)
We study finite measures on Bratteli diagrams invariant with respect to the tail equivalence relation. Amongst the proved results on the finiteness of measure extension, we characterize the vertices of a Bratteli diagram that support an ergodic finite invariant measure.